2015
DOI: 10.2355/isijinternational.55.528
|View full text |Cite
|
Sign up to set email alerts
|

Flow Behavior of Plastic Particles in the Lower Part of Blast Furnace

Abstract: Injection of plastics into blast furnaces as an alternative reducing agent has been carried out for the purpose of mitigation of carbon dioxide emissions. Several studies on the pyrolysis of plastic particles have been reported, however flow behavior of plastic particles or unburnt char in actual blast furnace is not clear.In this study, hotmodel experiments and thermogravimetry analysis were conducted for the modeling of gasification and combustion behavior of plastic particles, then flow behavior of plastic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Therefore, some researchers have proposed a hydrogen metallurgy process represented by blast furnace hydrogen-rich smelting technology, including blast furnace injection of coke oven gas, 1−4 coal manufacturing gas, and natural gas, 5,6 or other hydrogen-containing substances. 7,8 After the blast furnace is rich in hydrogen, the deterioration of coke in the blast furnace is mainly caused by the dissolution reaction. There are two different cases of coke dissolution reaction: one is the carbon dissolution reaction between coke and CO 2 , and the other is the water-gas reaction between coke and H 2 O.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, some researchers have proposed a hydrogen metallurgy process represented by blast furnace hydrogen-rich smelting technology, including blast furnace injection of coke oven gas, 1−4 coal manufacturing gas, and natural gas, 5,6 or other hydrogen-containing substances. 7,8 After the blast furnace is rich in hydrogen, the deterioration of coke in the blast furnace is mainly caused by the dissolution reaction. There are two different cases of coke dissolution reaction: one is the carbon dissolution reaction between coke and CO 2 , and the other is the water-gas reaction between coke and H 2 O.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen, as a reducing agent, causes no pollution and is an ideal substitute for carbon. Therefore, some researchers have proposed a hydrogen metallurgy process represented by blast furnace hydrogen-rich smelting technology, including blast furnace injection of coke oven gas, coal manufacturing gas, and natural gas, , or other hydrogen-containing substances. , …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the obtained result depends on the original coke reactivity and strength [46]. Another study revealed that char placed in coke pores can block the gas diffusion there and hinder in such a way the coke conversion [47]. A study on anthracite showed that CO 2 preferentially reacts with char, adhered to the coke surface, making SiC easier to form and wet the slag, which can enter pores and passivate gas from entering.…”
Section: Char Behaviour Outside the Racewaymentioning
confidence: 99%
“…14 Recently, it was reported that coarse particles move along with gas flow, and fine plastic injection is desirable for stable BF operation. 15 This study focuses on the reaction kinetics of the WP under raceway, bird's nest and shaft conditions. A wide range of analytical, laboratory and pilot facilities was applied to gain knowledge on separate stages of WP conversion, its injection behaviour, solution loss reaction and interaction with coke.…”
Section: Introductionmentioning
confidence: 99%